2013
DOI: 10.1002/joc.3707
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO

Abstract: A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
246
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 316 publications
(298 citation statements)
references
References 32 publications
29
246
3
1
Order By: Relevance
“…Similar trends have been observed in many parts of the world , including the Arabian region (Donat et al 2013). The warming trends in the percentile-based indices for Qatar are greater than the corresponding averages for the Arabian Peninsula, as mentioned before.…”
Section: Annual Variationsupporting
confidence: 84%
See 4 more Smart Citations
“…Similar trends have been observed in many parts of the world , including the Arabian region (Donat et al 2013). The warming trends in the percentile-based indices for Qatar are greater than the corresponding averages for the Arabian Peninsula, as mentioned before.…”
Section: Annual Variationsupporting
confidence: 84%
“…7, the increases in the number of warm days/nights occurred gradually during the 1980s, except for a sharp rise in the 1990s for both indices. Region-wide averaged results reported by Zhang et al (2005) and Donat et al (2013) have shown similar trends to the single-station results illustrated in Figs. 7 and 8.…”
Section: Annual Variationsupporting
confidence: 75%
See 3 more Smart Citations